OGUANG BAKAWEK ART IN MUARO PAITI TOWARDS SELLING INDUSTRY - Nursyirwan Nursyirwan; Alfalah Alfalah; Delfi Enida (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2023)
Tourism art is combination of ‘art domain’ and ‘tourism industry domain’. When it comes together, it would present a new kind of proper product called ‘tourism art’. The combination of those two domains inspires us to rise up the Village of Muaro Paiti which has various talents. Therefore, in the matter of actualizing Creative Industry program, the final aim of  the program is to prepare the Village of Muaro Paiti to be “art tourism of creative industry”. Traditional artists should be placed as business partner of tourism, not a worker of it who should obey and bow to tourism management, but they are expected to be able collaborating with the tourism instead. The exploitation of tourism operator or worker must soon be stopped due to the dense of visitation of international visitors who wish to closely see the uniqueness, speciality and high valuable of its arts and traditional cultures. The contribution of Creative Industry program in the future is to prepare Muaro Paiti society to be ready in collaboration with tourism department as a partner of art college: Indonesia Art Institute of Padangpanjang.Keywords: Oguang Bakawek; Tourism; Creative Industry..KESENIAN OGUANG BAKAWEK DI MUARO PAITI MENUJU INDUSTRI JUAL ABSTRAKSeni wisata merupakan perpaduan antara ‘domain seni’ dengan ‘domain industri pariwisata’. Bila keduanya bertemu akan menghadirkan satu jenis produk seni yang lazim disebut ‘seni wisata’. Pertemuan dua domain yang demikian menarik untuk dijadikan sumber inspirasi untuk mengangkat kesenian Oguang Bakawe di  Muaro Paiti, maka dalam rangka perwujudan kegiatan industri, satu capaian adalah Kenagarian Muaro Paiti siap menuju  industri jual, guna peningkatan taraf perekonomian rakyat.Seniman tradisi harus dipahami sebagai mitra bisnis pariwisata, bukan buruh pariwisata yang harus patuh dan tunduk pada manajemen pariwisata, namun dapat bekerjasama dengan pariwisata. Eksploitasi operator wisata terhadap seniman tradisional haruslah dihentikan mengingat wisatawan datang ke daerah-daerah tentu berkeinginan melihat dari dekat kekayaan seni dan budaya tradisional yang unik, khas, dan bernilai keaslian. Dampak dari kegiatan kreatifitas pendukung musik Saiyo di Muaro Paiti ke depannya masyarakat siap bekerjasama dengan pihak mitra dari Perguruan Tinggi Seni: Institut Seni Indonesia (ISI) PadangpanjangKata Kunci: Oguang Bakawek; Seni Pariwisata; Industri Kreatif.